Lighting impact on architectural modifaction of an adaptive reuse building: a case study of Tate Modern Gallery in the Sounthbank of London - Nur Amalina Hanapi; Leng, Pau Chung (Penerbit Universiti Kebangsaan Malaysia, 2022)
This research explores the analysis method of the current situation in Tate Modern, an adaptive reuse gallery that injects architectural intervention in terms of its massive modification from an industrial powerhouse station building to a gallery. Thus, exploration of lighting fundamentally and significantly impacts holistic and stage performance in the gallery design. However, there was a still few research that focused on the condition in lighting design performance for an adaptive reuse building of an industrial building to gallery. Therefore, this study explores design recommendations study made in the current state of the Tate Modern gallery as a methodology which includes passive and active design implications used recorded as part of the discussion. The result shows that the proposed design helped in lighting enhancement of the Tate Modern compound towards the Southbank area of London and how it injects end users' livability through its architectural modification through implementation of the skylight, upwards lighting, designated window, and sunbreak for the best rectification recommendation. Furthermore, the result of the study suggests such minimum glare and effective lighting distribution contribute to the amount reduction of energy consumption, improve the quality of reading, performance and properly enlighten the gallery activities and other exercises carried out to optimum brightness from its previous state as a powerhouse station.